Rekonstruksi Apokaliptis Antara Wahyu 22 1-5 Dengan Tradisi Kebo-Keboan - Ricky Atmoko; Andreas Hauw (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2022)
Abstract: "Kebo-keboan" tradition has been widely discussed in various journals nowadays. But no one has studied the gospel bridge from Christian apocalyptic literature with "kebo-keboan" tradition. The author asked, can the apocalyptic concept in Revelation 22:1-5 be a gospel bridge for the â€œkebo-keboanâ€ tradition? The author uses Paul Hiebert's critical contextualization concept as a research methodology. This methodological procedure consist of cultural analysis, Bible analysis, critical responses, and making new contextualization practices. From the cultural and Bible analysis, the author compares the vision receiver, apocalyptic environment, vision, and trancendent person. The author gives two critical response. The trancendent person replaced by God and the Lamb. The vision receiver, apocalyptic environment, and the Using communityâ€™s vision is acceptable. The author proposes three things for the new contextualization practice. The sowing seeds practice can be seen as a consumnation from God through tree and water of life. Offerings can be interpreted as an expression of gratitude for God as He lifted the curse. Then the dependence and eminence of Dewi Sri are diverted to God. In conclusion, the writer proves that the apocalyptic concept in Revelation 22:1-5 can be a gospel bridge for the â€œkebo-keboanâ€ tradition.Â Keywords: Revelation 22:1-5, apocalyptic, kebo-keboan tradition, and critical contextualizationÂ Abstrak: Tradisi â€œkebo-keboanâ€ ramai diperbincangkan dalam banyak jurnal kekinian. Namun belum ada yang mengkaji jembatan injil dari literatur apokaliptik Kristen dengan tradisi â€œkebo-keboanâ€. Penulis bertanya, apakah konsep apokaliptik dalam Wahyu 22:1-5 dapat menjadi jembatan injil bagi tradisi â€œkebo-keboanâ€? Penulis memakai konsep kontekstualisasi kritis Paul Hiebert sebagai metodologi penelitian. Prosedur metodologi ini yaitu analisa kultur, analisa Alkitab, memberi respons kritis, serta membuat praktik kontekstualisasi baru. Dari analisa kultur dan Alkitab, penulis membandingkan sosok pahlawan yang menerima visi, lingkungan apokaliptik, visi yang diterima, dan pribadi transenden yang disembah. Penulis memberikan dua respon kritis. Respons pertama adalah pribadi transenden yang dipercayai masyarakat Using perlu diganti dengan Allah dan Anak Domba. Respons kedua adalah sosok pahlawan, lingkungan apokaliptik, dan visi yang diterima masyarakat Using dapat diterima. Penulis mengusulkan tiga hal dalam praktik yang diperbaharui. Penyemaian bibit dapat dilihat sebagai pemulihan Allah melalui pohon dan air kehidupan. Sesaji dapat dimaknai sebagai ungkapan syukur atas kutukan yang telah diangkat oleh Tuhan. Lalu kebergantungan dan keutamaan dari Dewi Sri dialihkan kepada Allah. Pada akhirnya penulis membuktikan bahwa konsep apokaliptik dalam Wahyu 22:1-5 dapat menjadi jembatan injil bagi tradisi kebo-keboan.Â Kata Kunci: Wahyu 22:1-5, apokaliptik, tradisi kebo-keboan, kontekstualisasi kritisÂ